2017
DOI: 10.2320/matertrans.mk201625
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of CaTiO<sub>3</sub> in Molten CaCl<sub>2</sub> - as Basic Understanding of Electrolysis

Abstract: Electrochemical decomposition of CaTiO 3 at the cathode was examined in a scheme of titanium metal production from natural deposit, Ilmenite (TiFeO 3 ). Based on the possible precipitation of CaTiO 3 from TiFeO 3 , the electrochemical decomposition of CaTiO 3 is here examined using combination of the calciothermic reduction and the electrolysis of CaO in the same molten salt. Inhomogeneous reduction in the cathodic basket is related with buoyancy of Ca and insuf cient dehydration. By optimizing the cooling con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(75 reference statements)
1
17
0
Order By: Relevance
“…In the case of metallothermic reduction of solid oxide XO x (s) using electrodeposited liquid metal (Me = Ca, Li, or their alloys), the morphology of Me near the cathode is crucial when the oxide is reduced in the following mechanism 8,9,12,22 :where the liquid Me works effectively to reduce XO x , even though the latter does not have any direct electrical contact with the cathode. Therefore, the reduction efficiency in this method is thought to be greatly affected by the morphology of the interface between the electrolytically deposited Me and molten salt.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of metallothermic reduction of solid oxide XO x (s) using electrodeposited liquid metal (Me = Ca, Li, or their alloys), the morphology of Me near the cathode is crucial when the oxide is reduced in the following mechanism 8,9,12,22 :where the liquid Me works effectively to reduce XO x , even though the latter does not have any direct electrical contact with the cathode. Therefore, the reduction efficiency in this method is thought to be greatly affected by the morphology of the interface between the electrolytically deposited Me and molten salt.…”
Section: Introductionmentioning
confidence: 99%
“…Ilmenite can be converted to CaTiO 3 through wet chemical treatments. Subsequently, the electrochemical decomposition of CaTiO 3 was studied by Suzuki et al 31,32) Inhomogeneous reduction in the cathodic basket is related to the buoyancy of Ca and insufficient dehydration. The rapid reduction of fine particles from the cathodic surface formed a rigid Ti layer, which impeded further reduction of the inner parts of the cathode.…”
Section: Optimization Of Os Process Parametersmentioning
confidence: 99%
“…A new Ti production process replacing the Kroll process is desired. Many researchers have been studying the innovative smelting process, [1][2][3][4][5][6][7] but those processes are still under development. In our laboratory, the direct electrowinning of liquid Ti has been studied in molten fluoride, and it was shown that Ti metal was obtained.…”
Section: Introductionmentioning
confidence: 99%